Response dynamics of midbrain dopamine neurons and serotonin neurons to heroin, nicotine, cocaine, and MDMA. Issue 1 (December 2018) - Wei, Chao; Han, Xiao; Weng, Danwei; Feng, Qiru; Qi, Xiangbing; Li, Jin; Luo, Minmin
Abstract Heroin, nicotine, cocaine, and MDMA are abused by billions of people. They are believed to target midbrain dopamine neurons and/or serotonin neurons, but their effects on the dynamic neuronal activity remain unclear in behaving states. By combining cell-type-specific fiber photometry of Ca2+ signals and intravenous drug infusion, here we show that these four drugs of abuse profoundly modulate the activity of mouse midbrain dopamine neurons and serotonin neurons with distinct potency and kinetics. Heroin strongly activates dopamine neurons, and only excites serotonin neurons at higher doses. Nicotine activates dopamine neurons in merely a few seconds, but produces minimal effects on serotonin neurons. Cocaine and MDMA cause long-lasting suppression of both dopamine neurons and serotonin neurons, although MDMA inhibits serotonin neurons more profoundly. Moreover, these inhibitory effects are mediated through the activity of dopamine and serotonin autoreceptors. These results suggest that the activity of dopamine neurons and that of serotonin neurons are more closely associated with the drug's reinforcing property and the drug's euphorigenic property, respectively. This study also shows that our methodology may facilitate further in-vivo interrogation of neural dynamics using animal models of drug addiction.